Separation of monophyletic groups into distinct genera should consider phenotypic discontinuities: the case of Lasiurini (Chiroptera: Vespertilionidae) - Novaes, Roberto Leonan M.; Garbino, Guilherme S. T.; Cláudio, Vinícius C.; Moratelli, Ricardo (Zootaxa, 2018)
Baird et al. (2015) split Lasiurus into three distinct genera (Aeorestes, Dasypterus and Lasiurus) based on tree topology and divergence times for the tribe Lasiurini. This arrangement has not been widely adopted by the scientific community and was criticized by Ziegler et al. (2016). More recently, Baird et al. (2017) reinforced the taxonomic arrangement of Lasiurini comprised by three genera. Baird et al. (2015, 2017) provided the most comprehensive phylogenetic analyses of Lasiurus and offer important insights on the phylogeny and alpha-taxonomy of the group. However, we disagree with the taxonomic arrangement proposed at the genus level and explain our point below.